Intercalation of urea into kaolinite for preparation of controlled realease fertilizer - Mahdavi, Fariba; Abdul Rashid, Suraya; Yusop, Mohd. Khanif (Chemical Industry & Chemical Engineering Quarterly, 2014)
Urea was intercalated between layers of kaolinite by dry grinding technique to be used for preparation of controlled release fertilizer. X-ray powder diffraction (XRPD)patterns confirmed the intercalation of urea into kaolinite by the significant expansion of the basal spacing of kaolinite layers from 0.710 to 1.090 nm. Fourier transform infrared spectroscopy (FT-IR) also confirmed the hydrogen bonding between urea and kaolinite. Based on CHNS elemental analysis, 20 wt.% urea was intercalated between kaolinite layers. The urea-inter-calated kaolinite was mixed with hydroxypropyl methylcellulose (HPMC) binder and was granulated to prepare the nitrogen-based controlled release fertilizer. To study the nitrogen release behavior of granules, ultraviolet/visible (UV-Vis) spectroscopy was used through the diacetyl monoxime (DAM) colorimetric method. The result of UV-Vis spectroscopy showed that intercalation of urea into kaolinite decreased the nitrogen release from 25.50 to 13.66% after 24 h and from 98.15 to 70.01% after 30 days of incubation in water. According to the results, the prepared controlled release fertilizer (CRF) behaved according to the standard for CRFs.